Fatigue properties of steel to aluminum transition joints produced by explosion welding. (October 2020) - Becker, Nicolas; Gauthier, David; Vidal, Edgar E.
Highlights: Explosion-welded junctions are equivalent to the traditional butt-welded joints. The load ratio of explosion welded junctions influences the slope of the Basquin model. The waveform interface is probably influencing the stress field in fatigue results. The steel-aluminum transition joints have steep fatigue life slopes. Abstract: This manuscript presents the results of designing and testing a novel fixturing device for determining the fatigue properties of explosive bonded metals. The fatigue strength of steel to aluminum transition joints in tensile and compression stresses are presented. Additionally, shear stress for different load ratios was also studied. The stress distribution in the specimens was verified by finite element analysis. The experimental tensile/compressive fatigue results show a comparable fatigue lifetime to the recommended IIW values. The shear fatigue strength of the explosion-welded junction tested in this study is equivalent to a traditional butt welded joint.